Pemanfaatan SEO dan Konten Digital sebagai Strategi Pemasaran Online pada UMKM - Ibrahim, Darmawansah (Fakultas Ekonomi dan Bisnis Institut Ilmu Sosial dan Bisnis Andi Sapada, 2024)
This study aims to analyze the utilization of Search Engine Optimization (SEO) and digital content as online marketing strategies to enhance the visibility and competitiveness of Micro, Small, and Medium Enterprises (MSMEs). In today’s increasingly competitive digital era, MSME actors are required to leverage internet-based marketing technologies to reach consumers more widely and effectively. This research employs a descriptive qualitative method using a case study approach involving several MSMEs in the culinary and fashion sectors that have implemented SEO strategies and digital content marketing. The results show that the application of SEO helps improve the ranking of MSME websites on search engines, making it easier for consumers to find products organically. Meanwhile, engaging and relevant digital content increases consumer interaction, trust, and loyalty. The synergy between SEO and digital content has a significant impact on sales growth and brand awareness among MSMEs. Therefore, optimizing marketing strategies based on SEO and digital content is a crucial step in supporting digital transformation and ensuring the sustainability of MSME businesses in the digital economy era.